A few notes on τοῦτο and τὸ τοιοῦτον in Plato, Tim. 49 d 4 – e 7 - Chesi, Giulia Maria (Hyperboreus, 2016)
The reading of τοῦτο and τὸ τοιοῦτον in Plato’s Tim. 49 d 4 – e 7 is discussed here. According to the standard interpretation of the passage (e. g. Taylor, Cornford, Gulley), Plato maintains that the elements air, water, earth and ﬁre are in constant transformation, and therefore that “something such-like” (τὸ τοιοῦτον) is the only possible predication for them. Such judgment is expressed in the form: “do not say ﬁre or water or earth or air is this but something such-like”. Recently, the traditional reading of passage 49 d 4 – e 7 has been questioned by Zeyl, who follows Cherniss’ interpretation closely. Zeyl argues that here Plato is not talking about the physical elements, or about the legitimacy of propositions such as “this is ﬁre”. On the contrary, Plato is addressing the epistemological criteria for the use of the words “ﬁre”, “air” etc. So Plato appears to maintain that it is impossible to call the ﬁre “ﬁre”, or the air “air”, because the physical elements are in constant transformation. It is my concern to examine at some length Zeyl’s understanding of this passage, and to clarify why we shall opt for the standard reading against Zeyl and Cherniss. My defense of the standard reading is based on logical arguments which have not been taken into consideration by previous scholarship, but that prove nonetheless to be crucial for a critical assessment of the passage in question.